Sleep Latency among High School Female Students who Dance Gambyong Pareanom - Tika Permata Sari; Much Syamsulhadi; Dian Nugroho (Nexus Kedokteran Klinik, 2016)
Introduction: Sleep is important to maintain homeostatic function and mental health. Previous study showed that mindfulness exercise can shorten sleep latency. In this study, Gambyong Pareanom dance is used as mindfulness exercise. This study aims to find out whether Gambyong Pareanom dance can influence sleep latency. Methods: This study is a quasi experimental study with the design of pretest and posttest. The study took place in SMA Negeri 4 Surakarta with 10th grade students as subjects. Subjects were taken in blind method and divided into two: control and treatment. Students in treatment group follow 8 week of Gambyong Pareanom dance practice. Data was collected using Pittsburgh Sleep Quality Index (PSQI) questionnaire. PSQI score was measured before and after treatment and is compared to control group. Independent variables are dancing and not dancing Gambyong Pareanom while the dependent variable is sleep quality. Data was analyzed using Wilcoxon test. Result: Treatment group experienced significant improvement in their sleep latency (p = 0,003). Keywords: sleep, physical activity, mindfulness, sleep latency, dance